A double hurdle approach for company further training behaviour and an empirical test of this using data from the IAB establishment panel - Renate Neubäumer; Susanne Kohaut (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2007)
In this paper the further training behaviour of firms is explained using a double hurdle approach: the first hurdle is that the further training of employees is worthwhile for the firms in general, the second hurdle is that demand for further training arises. The empirical test is conducted using data from the IAB establishment panel: by combining the balanced panel for three waves into a cross-section it is possible to determine the effect of extending the observation period for the provision of further training (probit estimates) and the intensity of further training (quasi-likelihood estimates). The results confirm the double hurdle approach: variables for capital intensity, innovation orientation and the employee structure have a significant impact on whether further training is generally worthwhile for the firms, and investment in data processing and in the field of communication as well as organisational changes are significant motivations for providing further training.
Keywords: 330; Weiterbildungsverhalten - Determinanten; betriebliche Weiterbildung; Betrieb; Qualifikationsbedarf; Weiterbildungsbedarf; Bildungsertrag; Kapitalintensität; Innovation; Beschäftigtenstruktur; technischer Wandel; informationstechnische Bildung; organisatorischer Wandel; Bildungsinvestitionen; Bildungsökonomie; IAB-Betriebspanel